OBJECTIVE AND BEHAVIOURAL TESTS FOR AUDIOLOGIC ASSESSMENT OF CHILDREN WITH SUSPECTED HEARING LOSS (Annual of the Faculty of Philosophy in Skopje, 2023)
Audiologic assessment of infants and young children with suspected hearing loss requires selection of differential diagnostic techniques that are age-appropriate and appropriate to the child’s developmental capabilities.Objective assessment includes electrophysiologic and electroacoustic methods: otoacoustic emissions, auditory brainstem response, auditory steady-state response, tympanometry and acoustic reflex. The use of behavioural methods in audiologic assessment requires a response from the patient. Depending on the child’s age, the following methods can be performed: visual reinforcement audiometry, conditioned play audiometry, pure tone audiometry, and speech audiometry.Audiologic assessment in infants and children provides estimation of auditory sensitivity, evaluation of the integrity of auditory system andidentification of possible intervention options in case of existing hearing loss. Early detection and treatment of hearing loss in childhood is essential to ensure optimal speech and language development in the early years of life and optimal school performance for older children.
Keywords: audiologic assessment; children; hearing loss